Talcum powder composite powder degradable master batch and preparation method thereof
Through the preparation method of talc composite powder, the problems of insufficient performance and high cost of degradable plastics are solved, and the material performance and cost reduction are improved.
Patent Information
- Application Number
- CN202510176412.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
AI Technical Summary
The processing performance of existing degradable plastics is insufficient, and the cost is high. The rigidity, thermal deformation temperature, dimensional stability and surface hardness of the material cannot meet the application requirements.
The talc composite powder is used as the degradable masterbatch, and is prepared by mixing, extruding, pelleting and drying of the composite powder, powder resin, coupling agent, dispersing agent, antioxidant, stearic acid, lubricant, compatible agent and chain extender in a specific proportion.
It improves the processing and use performance of degradable plastics, reduces costs, and enhances the rigidity, thermal deformation temperature, dimensional stability and surface hardness of the material.
Smart Images

Figure CN119875325A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of masterbatch preparation, and in particular to a talc composite powder degradable masterbatch and a preparation method thereof. Background Art
[0002] The invention and use of plastics have brought great convenience to people's daily lives, but the problem of plastic pollution is becoming increasingly serious. Since non-degradable plastic waste can generally stay in nature for 200 to 400 years, and some can stay for 500 years, it not only causes soil pollution, but also pollutes the air and water, causing huge environmental safety hazards. Therefore, the control of white pollution has become a hot topic of global concern. Proposing the concept of degradable plastics is an effective way to solve plastic pollution. Degradable plastics refer to a type of plastic whose products have various properties that can meet the use requirements, the performance remains unchanged during the shelf life, and after use, they can be degraded into environmentally friendly substances under natural environmental conditions. At present, the production technology and application market of degradable plastics are not mature enough, and degradable products need to be continuously improved. For example, there are two main reasons why typical supermarket shopping bags are difficult to promote in the market. One is that the price of non-degradable bags has doubled compared to the past; the other is that the performance of the bags cannot meet the application requirements.
[0003] Filling is one of the important application technologies of polymer materials, and plays an important role in reducing costs or improving certain properties of polymer materials, such as improving the mechanical properties, heat resistance, anti-aging properties of products, and reducing film viscosity. However, when using fillers, on the one hand, dust pollution is difficult to avoid, and on the other hand, it is difficult to mix filler powder with plastic for injection molding. Therefore, filling masterbatch came into being. Summary of the invention
[0004] The purpose of the present invention is to provide a talcum powder composite powder degradable masterbatch and a preparation method thereof, which are used to solve the technical problems in the prior art that the processing and use performance of degradable plastics is insufficient, the cost is high, and the rigidity, heat deformation temperature, dimensional stability and surface hardness of the materials cannot meet the application requirements.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a talc composite powder degradable masterbatch, which is composed of the following components in parts by weight: 75-80 parts of composite powder, 15-20 parts of powder resin, 0.5-0.8 parts of coupling agent, 0.5-1 parts of dispersant, 0.5-1 parts of antioxidant, 0.5-1 parts of stearic acid, 1-2 parts of lubricant, 1-2 parts of compatibilizer, and 0.5-1 parts of chain extender;
[0007] The composite powder is obtained by mixing and grinding talcum powder ore and calcite ore to obtain an intermediate powder, and then modifying the intermediate powder;
[0008] The mass ratio of the talc ore to the calcite ore is 1-3:0.5-1.5.
[0009] Furthermore, the powder resin is a copolymer of butylene adipate and butylene terephthalate;
[0010] The coupling agent includes a phosphate coupling agent, a silane coupling agent or a titanate coupling agent;
[0011] The dispersant includes high carbon fatty alcohol, alkylphenol or stearamide;
[0012] The antioxidant includes a phosphate antioxidant or a hindered phenol antioxidant;
[0013] The lubricant includes silicone oil, fatty acid amide or oleic acid;
[0014] The compatibilizer includes maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene;
[0015] The chain extender includes neopentyl glycol, hydroquinone or ethylenediamine.
[0016] Furthermore, the particle size of the powder resin is 180-250 meshes.
[0017] Furthermore, the grinding speed is 2500-3500 r / min, and the grinding time is 60-120 min.
[0018] Furthermore, a grinding aid is added during the grinding, and the amount of the grinding aid added is 5-9‰ of the total mass of the ore;
[0019] The grinding aid includes triethanolamine, sodium chloride and sodium acetate;
[0020] The mass ratio of triethanolamine, sodium chloride and sodium acetate is 2-4:1-2:1.
[0021] Furthermore, the modified modifier includes a dodecyl-modified terminal hydroxyl siloxane modifier or a dodecyltrimethoxysilane modifier, and the added amount of the modifier is 8‰ to 12‰ of the mass of the intermediate powder.
[0022] Furthermore, the modification temperature is 75-85° C., and the modification time is 20-40 min.
[0023] The present invention provides a method for preparing the above-mentioned talcum powder composite powder degradable masterbatch, and the preparation method comprises the following steps:
[0024] The composite powder, powder resin, coupling agent, dispersant, antioxidant, stearic acid, lubricant, compatibilizer and chain extender are sequentially mixed, extruded, pelletized and dried to obtain the product.
[0025] Furthermore, the mixing speed is 1000-1500 r / min, and the mixing time is 8-20 min.
[0026] Furthermore, the extrusion is carried out in a twin-screw extruder, the main engine speed of the twin-screw extruder is 300-400r / min, and the feeding speed is 30-80r / min;
[0027] The temperature of each zone of the twin-screw extruder is independently 150-170°C.
[0028] Beneficial effects of the present invention:
[0029] The talc composite powder degradable masterbatch prepared by the present invention can be applied to degradable plastics to help plastic processing, improve its processing performance and reduce costs, and improve the rigidity, heat deformation temperature, dimensional stability and surface hardness of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of the preparation process of the degradable masterbatch of talcum powder composite powder. DETAILED DESCRIPTION
[0031] The present invention provides a talc composite powder degradable masterbatch, which is composed of the following components in parts by weight: 75-80 parts of composite powder, 15-20 parts of powder resin, 0.5-0.8 parts of coupling agent, 0.5-1 parts of dispersant, 0.5-1 parts of antioxidant, 0.5-1 parts of stearic acid, 1-2 parts of lubricant, 1-2 parts of compatibilizer, and 0.5-1 parts of chain extender;
[0032] The composite powder is obtained by mixing and grinding talcum powder ore and calcite ore to obtain an intermediate powder, and then modifying the intermediate powder;
[0033] The mass ratio of the talc ore to the calcite ore is 1-3:0.5-1.5.
[0034] In the present invention, the content of the composite powder is preferably 78 parts by mass.
[0035] In the present invention, the content of the powder resin is preferably 18 parts by mass.
[0036] In the present invention, the content of the coupling agent is preferably 0.7 parts by mass.
[0037] In the present invention, the content of the dispersant is preferably 0.6 to 0.9 parts by mass, and more preferably 0.8 parts by mass.
[0038] In the present invention, the content of the antioxidant is preferably 0.6 to 0.9 parts by mass, and more preferably 0.8 parts by mass.
[0039] In the present invention, the content of stearic acid is preferably 0.6 to 0.9 parts by mass, more preferably 0.7 parts.
[0040] In the present invention, the content of the lubricant is preferably 1.2 to 1.8 parts by mass, and more preferably 1.5 parts by mass.
[0041] In the present invention, the content of the compatibilizer is preferably 1.2 to 1.8 parts by mass, and more preferably 1.5 parts by mass.
[0042] In the present invention, the content of the chain extender is preferably 0.6 to 0.9 parts by mass, and more preferably 0.7 parts by mass.
[0043] In the present invention, the powder resin is preferably a copolymer of butylene adipate and butylene terephthalate (PBAT);
[0044] The coupling agent includes a phosphate coupling agent, a silane coupling agent or a titanate coupling agent, preferably a titanate coupling agent;
[0045] The dispersant includes high carbon fatty alcohol, alkylphenol or stearamide, preferably stearamide;
[0046] The antioxidant includes a phosphate antioxidant or a hindered phenol antioxidant, preferably a hindered phenol antioxidant;
[0047] The lubricant comprises silicone oil, fatty acid amide or oleic acid, preferably oleic acid;
[0048] The compatibilizer includes maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene, preferably maleic anhydride grafted polypropylene;
[0049] The chain extender includes neopentyl glycol, hydroquinone or ethylenediamine, preferably neopentyl glycol.
[0050] In the present invention, the particle size of the powder resin is 180-250 mesh, preferably 200-240 mesh, and more preferably 220 mesh.
[0051] In the present invention, the talc ore and the calcite ore are respectively washed, first crushed and second crushed to obtain talc ore and calcite ore with a particle size of preferably 20 to 40 mm.
[0052] In the present invention, the silicon dioxide content of the talc ore is ≥60%, and the calcium carbonate content of the calcite ore is ≥98%.
[0053] In the present invention, the grinding speed is 2500-3500 r / min, preferably 2800-3200 r / min, and more preferably 3000 r / min.
[0054] In the present invention, the grinding time is 60 to 120 min, preferably 80 to 100 min, and more preferably 90 min.
[0055] In the present invention, the mass ratio of the talc ore to the calcite ore is preferably 2:1.
[0056] In the present invention, the grinding is performed by ball milling, followed by classification by a classifier, and the obtained powder particle size D97 is preferably 4.5 to 5.5 μm.
[0057] In the present invention, the grinding media of the ball mill are preferably zirconia beads, and the ball-to-material ratio is preferably 2 to 2.2:1, and more preferably 2.1:1.
[0058] In the present invention, a grinding aid is added during the grinding, and the amount of the grinding aid added is 5-9‰ of the total mass of the ore, preferably 8‰;
[0059] The grinding aid is preferably a mixture of triethanolamine, sodium chloride, sodium acetate and salt substances;
[0060] The mass ratio of triethanolamine, sodium chloride and sodium acetate is 2-4:1-2:1, preferably 3:2:1.
[0061] In the present invention, the grinding aid also includes salt substances, preferably sodium tripolyphosphate and / or sodium hexametaphosphate, more preferably sodium tripolyphosphate or sodium hexametaphosphate, more preferably sodium hexametaphosphate, and the added amount of the salt substance is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate.
[0062] In the present invention, the grinding is to mix the talc ore, the calcite ore and the additive and then pump them into the ball mill at a speed of preferably 20 kg / h.
[0063] In the present invention, after the grinding aid enters the grinding system, it can eliminate the accumulation between powder particles, increase the dispersibility and fluidity between particles, shorten the residence time of the material in the mill, reduce the material filling rate, and improve the powder selection efficiency of the powder classifier.
[0064] In the present invention, the modified modifier includes a dodecyl-modified terminal hydroxyl siloxane modifier or a dodecyltrimethoxysilane modifier, preferably a dodecyltrimethoxysilane modifier, and the amount of the modifier added is 8‰ to 12‰ of the mass of the intermediate powder, preferably 10‰.
[0065] In the present invention, the modification temperature is 75 to 85° C., preferably 78 to 82° C., and more preferably 80° C.; the modification time is 20 to 40 min, preferably 25 to 35 min, and more preferably 30 min.
[0066] In the present invention, the modified material can form a covering film on the surface of the composite powder to improve its dispersibility and fluidity, and can also better couple with the resin to improve the mechanical properties and flame retardant properties of the plastic.
[0067] The present invention provides a method for preparing the above-mentioned talcum powder composite powder degradable masterbatch, and the preparation method comprises the following steps:
[0068] The composite powder, powder resin, coupling agent, dispersant, antioxidant, stearic acid, lubricant, compatibilizer and chain extender are sequentially mixed, extruded, pelletized and dried to obtain the product.
[0069] In the present invention, the mixing speed is 1000-1500 r / min, preferably 1200 r / min, and the mixing time is 8-20 min, preferably 10-18 min, and more preferably 15 min.
[0070] In the present invention, the extrusion is carried out in a twin-screw extruder, the main engine speed of the twin-screw extruder is 300-400r / min, preferably 320-380r / min, more preferably 350r / min, and the feeding speed is 30-80r / min, preferably 40-60r / min, more preferably 50r / min.
[0071] In the present invention, the temperature of each zone of the twin-screw extruder is independently 150-170°C, preferably 150°C in zone one, 155°C in zone two, 155°C in zone three, 160°C in zone four, 165°C in zone five, 170°C in zone six, 170°C in zone seven, 165°C in zone eight, 165°C in zone nine, 160°C in zone ten, and 160°C in zone eleven.
[0072] In the present invention, the head temperature of the twin-screw extruder is preferably 160°C.
[0073] In the present invention, the average particle size of the masterbatch after pelletizing is preferably 3 mm.
[0074] In the present invention, the pelletized product is dried and packaged to obtain the final product.
[0075] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0076] Example 1
[0077] Take talcum powder ore, calcite ore and 7‰ of the total mass of the ore (triethanolamine: sodium chloride: sodium acetate = 3:2:1, the mass of sodium hexametaphosphate is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate) in a mass ratio of 2:1 and pump them into a ball mill at a speed of 20kg / h, use zirconium oxide as a ball milling medium, grind for 60min under the conditions of a ball-to-material ratio of 2.2:1 and a rotation speed of 3000r / min, and then classify them with a classifier to obtain an intermediate powder with a powder particle size D97 of 5.2μm, which is transmitted to a continuous modifier by wind power, and 8‰ of dodecyl-modified terminal hydroxyl siloxane modifier is added, and react at 85°C for 30min to obtain a composite powder;
[0078] The PBAT resin is ground to a powder fineness of 200 mesh;
[0079] 75 parts of composite powder, 20 parts of powder resin, 0.5 parts of tetra-n-butoxy titanate, 0.8 parts of stearamide, 0.5 parts of antioxidant 1010, 0.7 parts of stearic acid, 1 part of oleic acid, 1 part of maleic anhydride grafted polypropylene and 0.5 parts of neopentyl glycol were mixed in a high-speed mixer at a speed of 1200 r / min for 10 minutes, and then the mixture was put into a twin-screw extruder at a main engine speed of 350 r / min and a feed speed of 50r / min, the temperatures of each zone of the twin-screw extruder are 150℃ for zone 1, 155℃ for zone 2, 155℃ for zone 3, 160℃ for zone 4, 165℃ for zone 5, 170℃ for zone 6, 170℃ for zone 7, 165℃ for zone 8, 165℃ for zone 9, 160℃ for zone 10 and 160℃ for zone 11. The extrusion is carried out at a head temperature of 160℃. The pellets are cut into masterbatches with an average particle size of 3mm. After drying, they become degradable masterbatches of talcum composite powder.
[0080] Example 2
[0081] Take talcum powder ore, calcite ore and 7‰ of the total mass of the ore (triethanolamine: sodium chloride: sodium acetate = 3:2:1, the mass of sodium hexametaphosphate is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate) in a mass ratio of 2:1 and pump them into a ball mill at a speed of 20kg / h, use zirconium oxide as a ball milling medium, grind for 90min under the conditions of a ball-to-material ratio of 2.2:1 and a rotation speed of 3000r / min, and then classify them with a classifier to obtain an intermediate powder with a powder particle size D97 of 4.6μm, which is transmitted to a continuous modifier by wind power, and 10‰ of dodecyltrimethoxysilane modifier is added, and react at 80°C for 30min to obtain a composite powder;
[0082] The PBAT resin is ground to a powder fineness of 200 mesh;
[0083] 75 parts of composite powder, 20 parts of powder resin, 0.5 parts of tetra-n-butoxy titanate, 0.8 parts of stearamide, 0.5 parts of antioxidant 1010, 0.7 parts of stearic acid, 1 part of oleic acid, 1 part of maleic anhydride grafted polypropylene and 0.5 parts of neopentyl glycol were mixed in a high-speed mixer at a speed of 1200 r / min for 10 minutes, and then the mixture was put into a twin-screw extruder at a main engine speed of 350 r / min and a feed speed of 50r / min, the temperatures of each zone of the twin-screw extruder are 150℃ for zone 1, 155℃ for zone 2, 155℃ for zone 3, 160℃ for zone 4, 165℃ for zone 5, 170℃ for zone 6, 170℃ for zone 7, 165℃ for zone 8, 165℃ for zone 9, 160℃ for zone 10 and 160℃ for zone 11. The extrusion is carried out at a head temperature of 160℃. The pellets are cut into masterbatches with an average particle size of 3mm. After drying, they become degradable masterbatches of talcum composite powder.
[0084] Example 3
[0085] Take talcum powder ore, calcite ore and 7‰ of the total mass of the ore (triethanolamine: sodium chloride: sodium acetate = 3:2:1, the mass of sodium hexametaphosphate is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate) in a mass ratio of 2:1 and pump them into a ball mill at a speed of 20kg / h, use zirconium oxide as a ball milling medium, grind for 90min under the conditions of a ball-to-material ratio of 2.2:1 and a rotation speed of 3000r / min, and then classify them with a classifier to obtain an intermediate powder with a powder particle size D97 of 4.5μm, which is transmitted to a continuous modifier by wind power, and 10‰ of dodecyltrimethoxysilane modifier is added, and react at 75°C for 30min to obtain a composite powder;
[0086] The PBAT resin is ground to a powder fineness of 200 mesh;
[0087] 75 parts of composite powder, 20 parts of powder resin, 0.5 parts of tetra-n-butoxy titanate, 0.8 parts of stearamide, 0.5 parts of antioxidant 1010, 0.7 parts of stearic acid, 1 part of oleic acid, 1 part of maleic anhydride grafted polypropylene and 0.5 parts of neopentyl glycol were mixed in a high-speed mixer at a speed of 1200 r / min for 10 minutes, and then the mixture was put into a twin-screw extruder at a main engine speed of 350 r / min and a feed speed of 50r / min, the temperatures of each zone of the twin-screw extruder are 150℃ for zone 1, 155℃ for zone 2, 155℃ for zone 3, 160℃ for zone 4, 165℃ for zone 5, 170℃ for zone 6, 170℃ for zone 7, 165℃ for zone 8, 165℃ for zone 9, 160℃ for zone 10 and 160℃ for zone 11. The extrusion is carried out at a head temperature of 160℃. The pellets are cut into masterbatches with an average particle size of 3mm. After drying, they become degradable masterbatches of talcum composite powder.
[0088] Example 4
[0089] Take talcum powder ore, calcite ore and 7‰ of the total mass of the ore (triethanolamine: sodium chloride: sodium acetate = 3:2:1, the mass of sodium hexametaphosphate is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate) in a mass ratio of 2:1 and pump them into a ball mill at a speed of 20kg / h, use zirconium oxide as a ball milling medium, grind for 90min under the conditions of a ball-to-material ratio of 2.1:1 and a rotation speed of 3000r / min, and then classify them with a classifier to obtain an intermediate powder with a powder particle size D97 of 4.6μm, which is pneumatically transmitted to a continuous modifier, 12‰ of dodecyltrimethoxysilane modifier is added, and react at 80°C for 30min to obtain a composite powder;
[0090] The PBAT resin is ground to a powder fineness of 200 mesh;
[0091] 75 parts of composite powder, 20 parts of powder resin, 0.5 parts of tetra-n-butoxy titanate, 0.8 parts of stearamide, 0.5 parts of antioxidant 1010, 0.7 parts of stearic acid, 1 part of oleic acid, 1 part of maleic anhydride grafted polypropylene and 0.5 parts of neopentyl glycol were mixed in a high-speed mixer at a speed of 1200 r / min for 10 minutes, and then the mixture was put into a twin-screw extruder at a main engine speed of 350 r / min and a feed speed of 50r / min, the temperatures of each zone of the twin-screw extruder are 150℃ for zone 1, 155℃ for zone 2, 155℃ for zone 3, 160℃ for zone 4, 165℃ for zone 5, 170℃ for zone 6, 170℃ for zone 7, 165℃ for zone 8, 165℃ for zone 9, 160℃ for zone 10 and 160℃ for zone 11. The extrusion is carried out at a head temperature of 160℃. The pellets are cut into masterbatches with an average particle size of 3mm. After drying, they become degradable masterbatches of talcum composite powder.
[0092] Example 5
[0093] Take talcum powder ore, calcite ore and 7‰ of the total mass of the ore (triethanolamine: sodium chloride: sodium acetate = 3:2:1, the mass of sodium hexametaphosphate is 10% of the sum of the mass of triethanolamine, sodium chloride and sodium acetate) in a mass ratio of 2:1 and pump them into a ball mill at a speed of 20kg / h, use zirconium oxide as a ball milling medium, grind for 90min under the conditions of a ball-to-material ratio of 2:1 and a rotation speed of 3000r / min, and then classify them with a classifier to obtain an intermediate powder with a powder particle size D97 of 4.6μm, which is transmitted to a continuous modifier by wind power, and 12‰ of dodecyltrimethoxysilane modifier is added, and react at 80°C for 30min to obtain a composite powder;
[0094] The PBAT resin is ground to a powder fineness of 200 mesh;
[0095] 80 parts of composite powder, 15 parts of powder resin, 0.5 parts of tetra-n-butoxy titanate, 0.8 parts of stearamide, 0.5 parts of antioxidant 1010, 0.7 parts of stearic acid, 1 part of oleic acid, 1 part of maleic anhydride grafted polypropylene and 0.5 parts of neopentyl glycol were mixed in a high-speed mixer at a speed of 1200 r / min for 10 minutes, and then the mixture was put into a twin-screw extruder at a main engine speed of 350 r / min and a feed speed of 50r / min, the temperatures of each zone of the twin-screw extruder are 150℃ for zone 1, 155℃ for zone 2, 155℃ for zone 3, 160℃ for zone 4, 165℃ for zone 5, 170℃ for zone 6, 170℃ for zone 7, 165℃ for zone 8, 165℃ for zone 9, 160℃ for zone 10 and 160℃ for zone 11. The extrusion is carried out at a head temperature of 160℃. The pellets are cut into masterbatches with an average particle size of 3mm. After drying, they become degradable masterbatches of talcum composite powder.
[0096] Comparative Example 1
[0097] Different from Example 1, in this comparative example, the composite powder is replaced by a commercially available talc masterbatch having a talc silicon content of 61% and a particle size D97 of 5 μm.
[0098] Table 1 shows the test indicators of the composite powders obtained in Examples 1 to 5.
[0099] Table 1 Detection indexes of composite powders obtained in Examples 1 to 5
[0100] Example 1 Example 2 Example 3 Example 4 Example 5 D97 / μm 5.2 4.6 4.5 4.6 4.6 D50 / μm 2.5 2.1 2.0 2.1 2.1 Activation degree / % 96.3 97.2 97.6 97.3 97.3
[0101] Table 2 shows the detection indexes of the masterbatches obtained in Examples 1 to 5 and Comparative Example 1.
[0102] Table 2 Detection indexes of masterbatches obtained in Examples 1 to 5 and Comparative Example 1
[0103] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Melt index g / 10min 2.96 3.12 3.26 3.22 3.09 2.85 Whiteness / % 89 90.5 91.0 90.6 90.6 88.6
[0104] Application Example 1
[0105] The masterbatches obtained in Examples 1 to 5 and Comparative Example 1 were respectively applied to the preparation of degradable plastics according to the formula in Table 3 (by mass fraction), and their mechanical properties, tensile strength, and elongation at break were tested according to standard GB / T1040-2018. The results are shown in Table 4.
[0106] Table 3 Formulation of degradable plastic in Application Example 1
[0107]
[0108]
[0109] Table 4 Performance test results of products obtained in Application Example 1
[0110]
[0111] As can be seen from the above embodiments, the present invention provides a talcum powder composite powder degradable masterbatch and a preparation method thereof. As can be seen from Table 4, the talcum powder composite powder degradable masterbatch of the present invention has better processing performance and better fluidity when applied to degradable plastics, improves the mechanical properties of the product, and can effectively reduce costs and reduce dust pollution in plastic production enterprises. The technical problems of insufficient processing and use performance of degradable plastics in the prior art, high cost, and inability of the material rigidity, heat deformation temperature, dimensional stability, and surface hardness to meet application requirements are solved.
[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A talcum powder composite powder degradable masterbatch, characterized in that: The invention is composed of the following components in parts by weight: 75-80 parts of composite powder, 15-20 parts of powder resin, 0.5-0.8 parts of coupling agent, 0.5-1 parts of dispersant, 0.5-1 parts of antioxidant, 0.5-1 parts of stearic acid, 1-2 parts of lubricant, 1-2 parts of compatibilizer and 0.5-1 parts of chain extender; The composite powder is obtained by mixing and grinding talcum powder ore and calcite ore to obtain an intermediate powder, and then modifying the intermediate powder; The mass ratio of the talc ore to the calcite ore is 1-3:0.5-1.
5.
2. The talc composite powder degradable masterbatch according to claim 1, characterized in that: The powder resin is a copolymer of butylene adipate and butylene terephthalate; The coupling agent includes a phosphate coupling agent, a silane coupling agent or a titanate coupling agent; The dispersant includes high carbon fatty alcohol, alkylphenol or stearamide; The antioxidant includes a phosphate antioxidant or a hindered phenol antioxidant; The lubricant includes silicone oil, fatty acid amide or oleic acid; The compatibilizer includes maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene; The chain extender includes neopentyl glycol, hydroquinone or ethylenediamine.
3. The talc composite powder degradable masterbatch according to claim 1 or 2, characterized in that: The particle size of the powder resin is 180-250 meshes.
4. The talc composite powder degradable masterbatch according to claim 1, characterized in that: The grinding speed is 2500-3500 r / min, and the grinding time is 60-120 min.
5. The talc composite powder degradable masterbatch according to claim 1 or 4, characterized in that: A grinding aid is added during the grinding, and the amount of the grinding aid added is 5-9‰ of the total mass of the ore; The grinding aid includes triethanolamine, sodium chloride and sodium acetate; The mass ratio of triethanolamine, sodium chloride and sodium acetate is 2-4:1-2:
1.
6. The talc composite powder degradable masterbatch according to claim 5, characterized in that: The modified modifier includes a dodecyl-modified terminal hydroxyl siloxane modifier or a dodecyl trimethoxy silane modifier, and the added amount of the modifier is 8‰ to 12‰ of the mass of the intermediate powder.
7. The talc composite powder degradable masterbatch according to claim 1 or 6, characterized in that: The modification temperature is 75-85° C., and the modification time is 20-40 minutes.
8. The method for preparing the degradable masterbatch of talc composite powder according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The composite powder, powder resin, coupling agent, dispersant, antioxidant, stearic acid, lubricant, compatibilizer and chain extender are sequentially mixed, extruded, pelletized and dried to obtain the product.
9. The method for preparing a degradable masterbatch of talc composite powder according to claim 8, characterized in that: The mixing speed is 1000-1500 r / min, and the mixing time is 8-20 min.
10. The method for preparing a degradable masterbatch of talc composite powder according to claim 8 or 9, characterized in that: The extrusion is carried out in a twin-screw extruder, the main engine speed of the twin-screw extruder is 300-400r / min, and the feeding speed is 30-80r / min; The temperature of each zone of the twin-screw extruder is independently 150-170°C.